Impact of tropospheric tides on the nitric oxide 5.3 μm infrared cooling of the low‐latitude thermosphere during solar minimum conditions. Issue 11 (5th November 2013) - Oberheide, J.; Mlynczak, M. G.; Mosso, C. N.; Schroeder, B. M.; Funke, B.; Maute, A.
<x xml:space="preserve">Abstract</x> [1] This paper explores the impact of diurnal tides that begin near the surface as heat is released by evaporation and condensation on Earth's upper atmosphere natural thermostat: the nitric oxide (NO) infrared cooling of the thermosphere at 5.3 μm. Equatorial NO volume emission rate measurements from 100 to 180 km made by Sounding of the Atmosphere using Broadband Emission Radiometry (SABER) on TIMED during the solar minimum year 2008 are analyzed on two important nonmigrating tides, the DE2 and DE3 components. DE3 (DE2) amplitudes maximize around 125 km altitude and, depending on season, are on the order of 0.18 (0.16) nW/m3. This represents a substantial modulation of the mean NO emission that maximizes in the same altitude range with a value of about 0.8 nW/m3. Tropospheric tides are therefore important not only for the dynamics and electrodynamics of the ionosphere‐thermosphere system but also for modulating the thermospheric energy budget. Supporting photochemical tidal modeling indicates that the main tidal coupling mechanism is the temperature dependence of the collisional excitation of the NO (ν=1) vibrational state. However, the response to vertical tidal advection is also important. It is in‐phase with the response to temperature and contributes as much as 50% to the NO tides at and above the emission maximum. Neutral density tidal variations contribute about 25% but with a 9 h phase offset resulting in a net damping. These results imply that NO 5.3 μm emissions are a suitable proxy for studying tidal dynamics in the thermosphere where no global temperature measurements are available.